2016
DOI: 10.1016/j.ijid.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and mass gatherings—opportunities for defining burden, transmission risk, and the optimal surveillance, prevention, and control measures at the annual Hajj pilgrimage

Abstract: Tuberculosis (TB) is now the most common infectious cause of death worldwide. In 2014, an estimated 9.6 million people developed active TB. There were an estimated three million people with active TB including 360000 with multidrug-resistant TB (MDR-TB) who were not diagnosed, and such people continue to fuel TB transmission in the community. Accurate data on the actual burden of TB and the transmission risk associated with mass gatherings are scarce and unreliable due to the small numbers studied and methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
21
2
Order By: Relevance
“…Further studies are required to define the scale of the tuberculosis during the Hajj and to develop proactive screening, treatment, and prevention guidelines. 92 Several studies also done on enteric pathogens during the Hajj show the emergence of antibioticresistant bacteria (appendix). 33,34,93 To prevent emergence of and spread of antibioticresistant bacteria, antibiotic pre scription and consumption by pilgrims at mass gathering events should be rationalised and regulated.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…Further studies are required to define the scale of the tuberculosis during the Hajj and to develop proactive screening, treatment, and prevention guidelines. 92 Several studies also done on enteric pathogens during the Hajj show the emergence of antibioticresistant bacteria (appendix). 33,34,93 To prevent emergence of and spread of antibioticresistant bacteria, antibiotic pre scription and consumption by pilgrims at mass gathering events should be rationalised and regulated.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…1 Mortality from TB in 2015 reached 1.8 million, making it one of the top ten causes of death worldwide. 1,2 International travel, mass gathering events, and migration facilitate the spread of TB. In this context, the Kingdom of Saudi Arabia (KSA) is particularly relevant because of its hosting of the Hajj, where annually around 2 million pilgrims from over 180 countries visit KSA.…”
Section: Introductionmentioning
confidence: 99%
“…Scanty data are available on the prevalence of active TB during Hajj, and there have been no specific studies to define the burden of TB during the pilgrimage. 2 Evidence of TB in pilgrims comes from clinical studies of causes of hospital admissions during Hajj which reported the isolation of Mycobacterium tuberculosis from 5% to 28% of patients with pneumonia during the event. 2,5 Given the short duration of the Hajj pilgrimage, these active TB cases are likely to be either imported or reactivated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some infections like tuberculosis have a long incubation period of several years, and exposure at a mass gathering will not be apparent and may easily be overlooked. 12 The transmission of multidrug-resistant bacteria, for instance Gram-negative bacteria hosted in the intestine, is another concern that has not been well studied. Asymptomatic individuals are colonized with local bacteria and may be carriers for months.…”
Section: Spread Of Pathogens Between Healthy Asymptomatic Individualsmentioning
confidence: 99%